De la pertinence d’une déclaration de risque inexacte à propos d’une garantie d’exonération de prime dans une assurance sur la vie : coordonnées de référence et qualification - Lluelles, Didier (Assurances)

(untitled) (HEC Montréal, 1987)
Mr. Didier Lluelles, lawyer, examines the scope of the additional insurance endorsement which makes it possible to maintain in force life insurance policies without payment of premiums, in the event of the insured's disability. With the permission of the author and of the journal Thémis, we are pleased to present Mr. Lluelles' text. Unfortunately, space constraints do not allow us to reproduce the foot-notes which followed the article. These may, however, be found in the abovementioned journal, volume 20, number 3.